Association of the HtrA1 rs11200638 Polymorphism with Neovascular Age-Related Macular Degeneration in Indonesia - Supanji, Supanji; Perdamaian, Ayudha Bahana Ilham; Romdhoniyyah, Dewi Fathin; Sasongko, Muhammad Bayu; Agni, Angela Nurini; Wardhana, Firman Setya; Widayanti, Tri Wahyu; Prayogo, Muhammad Eko; Oka, Chio; Kawaichi, Masashi (Springer, 2021)
Introduction: The aim of this study was to investigate the association of the HtrA1 rs11200638 polymorphism with neovascular age-related macular degeneration (nAMD) in Indonesia. Methods: This case–control study included 80 patients with nAMD and 85 controls. Demographic parameters and whole blood were collected from each participant. Genomic DNA was extracted and used to assess the rs11200638 genotype by PCR and restriction enzyme digestion. Associations between the HtrA1 rs11200638 polymorphism and other risk factors for susceptibility to nAMD were assessed using the logistic regression model. Results: Significant allelic associations between the HtrA1 polymorphism and nAMD were detected (odds ratio [OR] 8.67; 95% confidence interval [CI] 4.88–15.41; P \ 0.001). Genotype analysis showed a statistical difference between the nAMD group and the control group (P \ 0.001). In the multiple adjusted logistic regression model, people with the AA genotype were more likely to have nAMD although there was a wide confidence interval (OR 19.65; 95% CI 4.52–85.38; P \ 0.001). Conclusion: Our findings show that the risk of nAMD increased in the presence of risk alleles of HtrA1 rs11200638.